SARS-CoV-2 Neutralization Assay System using Pseudo-lentivirus - Anastasia Armimi; Afina Firdaus Syuaib; Katherine Vanya; Marselina Irasonia Tan; Dessy Natalia; David Virya Chen; Chikako Ono; Yoshiharu Matsuura; Anita Artarini; Ernawati Arifin Giri-Rachman (Indonesian Biomedical Journal, 2023)
BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infects humans' lower respiratory tracts and causes coronavirus disease-2019 (COVID-19). Neutralizing antibodies is one of the adaptive immune system responses that can reduce SARS-CoV-2 infection. This study aimed to develop a SARS-CoV-2 neutralization assay system using pseudo-lentivirus.